Reply: Impaired mitochondrial function abolishes gamma oscillations in the hippocampus through an effect on fast-spiking interneurons - Kann, Oliver; Huchzermeyer, Christine; Kovács, Richard; Wirtz, Stefanie; Schuelke, Markus (Brain, 2011)
Sir, We appreciate the letter of Whittaker et al. (2011) who report on the effects of metabolic stress on the properties of excitatory pyramidal cells and fast-spiking inhibitory interneurons during gamma oscillations. The authors combined extra- and intracellular electrophysiological recordings and pharmacology in rat hippocampal slices in vitro.Gamma oscillations are generally thought to represent a temporal matrix of higher brain functions and have been observed in all cortical brain structures, including the hippocampus (Bartos et al., 2007; Uhlhaas and Singer, 2010; Whittington et al., 2011). In hippocampal neuronal networks, the precise interaction of several types of inhibitory GABAergic interneurons (releasing neurotransmitter, γ-aminobutyric acid) and excitatory pyramidal cells is essential for the establishment of gamma oscillations. Inhibitory GABAergic interneurons are characterized by much higher action potential firing rates than excitatory pyramidal cells (Hájos et al., 2009). Highly active inhibitory interneurons are the axo-axonic cells and the parvalbumin-containing basket cells that have been reported to generate action potentials at ∼40 Hz during gamma oscillations or at ∼200 Hz during sharp-wave ripple activity (Ylinen et al., 1995; Penttonen et al., 1998; Klausberger et al., 2003). In many in vitro studies, gamma oscillations have been induced in hippocampal slice preparations by bath application of cholinergic receptor agonists (acetylcholine or carbachol; cholinergic model) or glutamatergic receptor agonist, kainic acid (kainate model). Both experimental models differ in the synaptic mechanisms underlying gamma oscillations (Bartos et al., 2007). However, more general conclusions can be drawn when taking results from both models into account.